2016
DOI: 10.1037/neu0000280
|View full text |Cite
|
Sign up to set email alerts
|

The beneficial influence of inattention on visual interference in schizophrenia.

Abstract: Schizophrenia patients likely pay less attention to stimuli in general; however, the impact of this impairment on target detection is compensated by relatively greater inattention to irrelevant components of the stimuli, and this explains why they are not more influenced by interference than healthy participants at the behavioral level. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 43 publications
3
6
0
Order By: Relevance
“…While earlier work included samples with a discrete diagnosis, our findings in this transdiagnostic sample suggest that higher severity of delusions/magical thinking is associated with reduced P1 amplitude, regardless of diagnosis. We did not find a P1 amplitude relationship with either clinician-rated or self-reported disorganized symptom measures, as found in two previous studies (Bedwell et al, 2015; Brodeur et al, 2016).…”
Section: 0 Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…While earlier work included samples with a discrete diagnosis, our findings in this transdiagnostic sample suggest that higher severity of delusions/magical thinking is associated with reduced P1 amplitude, regardless of diagnosis. We did not find a P1 amplitude relationship with either clinician-rated or self-reported disorganized symptom measures, as found in two previous studies (Bedwell et al, 2015; Brodeur et al, 2016).…”
Section: 0 Discussionsupporting
confidence: 78%
“…Our first hypothesis was partially supported as we found that, across the entire sample, individuals with increased scores on clinician-rated PANSS Delusions (across both contrasts; see Figure 1) and the related self-report scale of SPQ-BR Magical Thinking (in the 8% contrast; see Figure 2), showed a reduced averaged bilateral P1 amplitude on the gray background. These relationships involving delusions/magical thinking are consistent with a study examining a schizophrenia sample (Gonzalez-Hernandez et al, 2014) and in a nonpsychiatric sample (Bedwell et al, 2013), but is inconsistent with one study that examined the PANSS Delusions item relationship to P1 amplitude in a schizophrenia sample and did not find a relationship (Brodeur et al, 2016). While earlier work included samples with a discrete diagnosis, our findings in this transdiagnostic sample suggest that higher severity of delusions/magical thinking is associated with reduced P1 amplitude, regardless of diagnosis.…”
Section: 0 Discussionsupporting
confidence: 44%
See 3 more Smart Citations